Pengaruh Kenaikan Harga Pakan terhadap Permintaan Pakan, Produktivitas dan Pendapatan Usaha Pembesaran Ikan Nila pola Kolam Air Deras - Karyana KS (Paspalum: Jurnal Ilmiah Pertanian, 2011)
This study aims to determine the effect of rising feed prices on the use of feed, pond productivity and business income of tilapia fish enlargement. The research method used is a periodical survey of indigenous fish farmers with census techniques. The analysis technique used is multiple regression with the rank function model and one way variance analysis. The data used in the form of panel data from 2009-2010. Based on the result of research, it is found that the increase of feed price has an effect on decreasing amount of feed usage (demand), decreasing of pond productivity and business income